Do ordinário ao extraordinário: o tipo criminoso em Nietzsche - Diogo, Luana Mara (2023)
This dissertation seeks to clarify the characterization of the criminal type, based on Friedrich Nietzsche's thought, especially in works written between 1878 and 1888. Although this typology appears occasionally in some aphorisms, it is linked to important notions investigated by the German philosopher, such as morality, free will and punishment. In Nietzsche's works, the criminal is sometimes interpreted as a kind of "mental patient", incapable of making decisions, and sometimes as a strong person who, under social pressures, degenerates. In both cases, such type is interpreted as an offender, unable to submit to the moral values established by the community to which they belong. The criminal puts the social organization itself at risk, because this kind of person acts according to their instincts and not rationally, as every individual should act. The predominance of instincts over reason would be in contradiction to the notion of free will supported by Judeo-Christian morality, which presupposes that acting freely is a consequence of the rational capacity shared by all human beings. In order to understand this type, it is necessary to follow the genealogical path undertaken by Nietzsche to determine the origin of guilt and punishment, and to identify, apart from what characterizes the criminal, which role such character plays in different societies.